Prescribing antibiotics by dentists in Colombia: Toward a conscientious prescription (2020)
Objectives: Inappropriate prescription of antibiotics contributes to antibiotic resistance. Therefore, the objective of this study was to determine the awareness, attitudes, and intention to practice of dentists prescribing antibiotics in Colombia in order to design a virtual learning environment on this subject. Methods: In a descriptive study across seven cities, 700 dentists from different Colombian cities were requested to complete a validated questionnaire containing five sections: general information, awareness on antibiotic effectiveness and antibiotic resistance, attitudes regarding prescription decision, intention to practice concerning clinical cases, and complementary information. The level of awareness, attitudes, and intention to practice was determined and Chi-square test was used to determine the existence of significant differences among cities. Results: The majority of dentists showed a medium level regarding the number of correct answers on awareness (62.4 percent) and attitudes (88.7 percent) and a high level on intention to practice (91.7 percent). Common errors within the awareness section included the meaning of the term “antibiotic resistance” (35 percent) and most dentists were not convinced that such resistance could be derived from prescription of antibiotics (51.2 percent). In the attitudes section, only 45 percent declared that they prescribe antibiotics based mainly on symptoms, and the intention to practice section showed a significant percentage of unnecessary prescription (51 percent for pacemaker users) or absence of prescription (53.9 percent for ventricular septal defect) in antibiotic prophylaxis for infectious endocarditis (IE). Conclusion: The dentists interviewed should be trained and made aware of antibiotic resistance, microbiological and clinical foundations, and current antibiotic prophylaxis guidelines.